УГОЛОВНО-КРИМИНОЛОГИЧЕСКИЕ АСПЕКТЫ ОРГАНИЗОВАННОЙ ПРЕСТУПНОСТИ - Исмаилова, З. (SCIENCE and SOCIETY, 2019)
Today the fight against organized crime is becoming one of the most urgent and problematic issues. The effectiveness of the fight against organized crime can be achieved by strengthening large-scale preventive measures of influence on socially dangerous or only established groups. This in its turn means a set of measures to systematize crime of a legal, organized and tactical nature.